2021
DOI: 10.1107/s2052520621001840
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, hydrogen bonds and thermal transformations of superprotonic conductor Cs6(SO4)3(H3PO4)4

Abstract: Crystals of Cs6(SO4)3(H3PO4)4 belong to the family of alkali metal acid salts that show a high protonic conductivity at relatively low temperatures. Such properties make superprotonic crystals an excellent choice for the study of the influence of the hydrogen subsystem on the physicochemical properties and promising materials for energy-efficient technologies. Single crystals of Cs6(SO4)3(H3PO4)4 were studied by neutron diffraction methods, optical polarization microscopy, scanning electron microscopy and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Nevertheless, the Cs 6 (SO 4 ) 3 (H 3 PO 4 ) 4 crystal itself does not float in this solution. Given that the density of the fluoroplastic is ~2.2 g/cm 3 , and the X-ray density of the crystal according to [15] is 3.191 g/cm 3 , the density of the solution lies in the range of values 2.2-3.191 g/cm 3 .…”
Section: Growing a Cs 6 (So 4 ) 3 (H 3 Po 4 ) 4 Crystal From Water So...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the Cs 6 (SO 4 ) 3 (H 3 PO 4 ) 4 crystal itself does not float in this solution. Given that the density of the fluoroplastic is ~2.2 g/cm 3 , and the X-ray density of the crystal according to [15] is 3.191 g/cm 3 , the density of the solution lies in the range of values 2.2-3.191 g/cm 3 .…”
Section: Growing a Cs 6 (So 4 ) 3 (H 3 Po 4 ) 4 Crystal From Water So...mentioning
confidence: 99%
“…At the same time, the crystal Cs 6 H(HSO 4 ) 3 (H 2 PO 4 ) 4 [14], formally not belonging to the CsHSO 4 -CsH 2 PO 4 system, was found. Subsequently, thanks to precision structural studies, it was found that a more correct structural formula for it would be Cs 6 (SO 4 ) 3 (H 3 PO 4 ) 4 [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is a continuation of our studies of superprotonic crystals M m H n (AO 4 ) (m+n)/2 •yH 2 O (M = K, Rb, Cs, NH 4 ; AO 4 = SO 4 , SeO 4 , HPO 4 , HAsO 4 ) by methods of structural analysis using X-ray, synchrotron radiation and neutrons. These studies also include complex caesium hydrogen sulfate phosphates Makarova, Selezneva et al, 2016;Mikheykin et al, 2017;Makarova et al, 2021;Komornikov et al, 2023), as well as the research of the real structure of the members of this family using electron and atomic force microscopy (Gainutdinov et al, 2021(Gainutdinov et al, , 2023Selezneva et al, 2023) in order to reveal regular relationships between their composition, structure and physical properties.…”
Section: Introductionmentioning
confidence: 99%